2019
DOI: 10.1097/md.0000000000016781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient age on outcomes after carotid endarterectomy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There were 2 cases of stroke with 1 in immediate postoperative period and another late stroke in patients, both occurred in the patients with age >60 years (p=0.134) which is similar to the study done by Jeong MJ et al which concluded that age is an independent risk factor for major adverse events following CEA within 4 years. 13 Summarizing, major complications occurred more frequently in the age group ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…There were 2 cases of stroke with 1 in immediate postoperative period and another late stroke in patients, both occurred in the patients with age >60 years (p=0.134) which is similar to the study done by Jeong MJ et al which concluded that age is an independent risk factor for major adverse events following CEA within 4 years. 13 Summarizing, major complications occurred more frequently in the age group ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have analyzed the associations between age and outcomes of CEA in Asian populations. Jeong et al [ 10 ] reported no significant difference in the risks of perioperative MACE and the 4-year overall incidence of cardiovascular events between younger and elderly patients in Korea. However, the age threshold was 60 years, which was not old enough to represent elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a range of reports discussing the role of statins in preventing carotid pathologies and highlighting their role in reducing the risk of ischemic stroke [38]. Some of them indicate that statins have an impact on the regression of pathological changes in the carotid artery [39].…”
Section: Discussionmentioning
confidence: 99%